Effect of antimicrobial extracts of Piper betle and Clinacanthus nutans on in vitro growth of selected fungal pathogens - Rahim, Nur Maliya (2016)
Plant pathogenic fungi have been identified as the causal agent of various types of plant diseases in agricultural crops in Malaysia. Due to this problem, many methods of control had been introduced. The most common method is by using chemical control. However, application of chemical fungicides causes a major destruction to the environment because of high synthetic toxicity elements. The use of Piper betle and Clinacanthus nutans extracts as biopesticides is a good application towards sustainable agriculture. In view of this, this research was conducted 1) to extract crude antimicrobial compounds from P.betle and C. nutans and 2) to investigate the effectiveness of different concentrations of crude antimicrobial extracts on the in vitro growth of selected plant fungal pathogens. The selected fungal pathogens were Rhizoctonia solani, Ganoderma boninense, Fusarium oxysporum f sp cubense and Exserohilum rostratum. The leaves were washed, air dried at room temperature and ground using a blender. The leaf powder were soaked in methanol and loaded in orbital shaker. The mixture was filtered and the filtrate was concentrated using rotary evaporator to obtain dried extract. There were four concentrations (5, 10, 15 and 20%) used and compared with control (0%). Poisoned agar plates with P. betle extract showed inhibition on the mycelial growth and number of spores. The percent inhibition of diameter growth (PIDG) of F.o.c was 94.04% at 12th day, G. boninense 89.42% at 12th day, R. solani 82.84% at 4th day and E. rostratum 43.74% at 8th day. The number of spores produced (4x106) in 20% by F.o.c in P.betle extract is 969 while for R.solani is 178. Poisoned agar plates with C. nutans extract showed PIDG of E.rostratum was 64.42% at 8th day R. solani 58.86% at 4th day, G. boninense 27.48% at 12th day and F.o.c 10.36% at 12th day. The number of spore produced (4x106) in 20% by F.o.c in C.nutans extract is 1723 while for R.solani is 38. Thus, this showed that the extracts of P. betle and C. nutans have the potential to be used as bio-fungicides as a safe alternative to synthetic fungicides.